When sun meets moon : gender, eros, and ecstasy in Urdu poetry - Kugle, Scott Alan (Islamic civilization & Muslim networks.)
"The two Muslim poets featured in Scott Kugle's comparative study lived separate lives during the eighteenth and early-nineteenth centuries in the Deccan region of southern India. Here, they meet in the realm of literary imagination, illuminating the complexity of gender, sexuality, and religious practice in South Asian Islamic culture. Kugle argues that Sun and Moon expressed through their poetry exceptions to the general rules of heteronormativity and gender inequality common in their patriarchal societies. Their art provides a lens for a more subtle understanding of both the reach and the limitations of gender roles in Islamic and South Asian culture and underscores how the arts of poetry, music, and dance are integral to Islamic religious life. Integrated throughout are Kugle's translations of Urdu and Persian poetry previously unavailable in English" --